CONTEXTUAL DISTANCE TEACHING TO IMPROVE TOURIST DRIVERS' ENGLISH LANGUAGE EXPRESSION - Wardana, I Ketut (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2024)
This study aimed to assess the effectiveness of Contextual Distance Teaching (CDT) in improving driver’s English language expression and enhancing motivation, while also evaluating its significant influence on their English proficiency. Utilizing an action research approach conducted via the WhatsApp online platform, this study engaged 10 tourist drivers associated with the Bali Transport group, aged between 22 and 50. The study comprised two cycles, each consisting of three sessions. Data collection involved administering tests and questionnaires, including pretest, post-test 1, and post-test 2. Analysis was conducted using descriptive statistics and paired sample t-tests. The initial findings indicate that CDT effectively enhances the language expression of drivers in service-related contexts. The average pretest score, initially categorized as